Generated paths of an autocatalytic set of a secondary system of a pressurized water reactor - Mahamud, Z. (Penerbit UTM Press, 2017)
A graph is used to model pairwise relation between objects. In this paper, it is used to model secondary system of pressurized water reactor. The process is presented as a dynamic graph by integrating the concept of Autocatalytic Set (ACS). The graph is then transformed into an omega algebra whereby all the possible paths of the process are determined. Seven variables are identified to represent the nodes with twenty one links to indicate catalytic relations among these nodes. A programming code of C++ is developed for the identification of these 317 links.